2016
DOI: 10.1186/s13075-016-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel inflammatory biomarker, GlycA, associates with disease activity in rheumatoid arthritis and cardio-metabolic risk in BMI-matched controls

Abstract: BackgroundRA and CVD both have inflammation as part of the underlying biology. Our objective was to explore the relationships of GlycA, a measure of glycosylated acute phase proteins, with inflammation and cardiometabolic risk in RA, and explore whether these relationships were similar to those for persons without RA.MethodsPlasma GlycA was determined for 50 individuals with mild-moderate RA disease activity and 39 controls matched for age, gender, and body mass index (BMI). Regression analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 38 publications
1
39
1
1
Order By: Relevance
“…Atherothrombotic CVD is described as a chronic inflammatory condition, which involves processes mediated by cytokines and acute phase reactants . Indeed, higher CVD risk in chronic inflammatory conditions has been shown to be associated with higher GlycA levels . In addition, GlycA is shown to be associated with other measures of subclinical CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Atherothrombotic CVD is described as a chronic inflammatory condition, which involves processes mediated by cytokines and acute phase reactants . Indeed, higher CVD risk in chronic inflammatory conditions has been shown to be associated with higher GlycA levels . In addition, GlycA is shown to be associated with other measures of subclinical CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, GlycA also showed associations with BMI and fitness among adolescents 30 , suggesting its role even in the early stages of cardiometabolic dysfunction. Additionally, in inflammatory states, GlycA associated with disease activity as well as CHD among rheumatoid arthritis patients 15, 18 , and was elevated in patients with SLE compared to controls 16 . Finally, GlycA also associated with disease activity in SLE, and revealed improved levels subsequent to treatment 17 .…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have demonstrated GlycA to be a strong predictor of future CV events 11, 12 , incident type 2 diabetes 13, 14 , long-term risk of severe infection 4 , and overall mortality 12 . Moreover, GlycA showed promise in the assessment of disease activity, treatment response, and CAD in patients with inflammatory disorders, such as systemic lupus erythematosus (SLE) and rheumatoid arthritis 1518 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the growth of the C26 tumour leads to a significant increase in interleukin‐6 (IL‐6) levels, which correlate with the loss of body weight and lead to hepatic synthesis and secretion of acute phase proteins . In a recent study of rheumatoid arthritis, GlycA was significantly correlated with circulating IL‐6 . Some chemotherapeutics, such as cyclophosphamide‐doxorubicin‐5‐fluorouracil, can lead to increases in IL‐6 production, thus promoting changes in body composition and fatigue .…”
Section: Discussionmentioning
confidence: 99%